Climate change risks and food security in Bangladesh - Yu, Winston; Hassan, Ahmadul; Alam, Mozaharul; Khan Abu, Saleh; Ruane, Alex; Rosenzweig, Cynthia; Major, David C.; Thurlow, James (Routledge, 2010)
Managing climate variability and change remains a key development and food security issue in Bangladesh. Despite significant investments, floods, droughts, and cyclones during the last two decades continue to cause extensive economic damage and impair livelihoods. Climate change will pose additional risks to ongoing efforts to reduce poverty. This book examines the implications of climate change on food security in Bangladesh and identifies adaptation measures in the agriculture sector using a comprehensive integrated framework. First, the most recent science available is used to characterize current climate and hydrology and its potential changes. Second, country-specific survey and biophysical data is used to derive more realistic and accurate agricultural impact functions and simulations. A range of climate risks (i.e. warmer temperatures, higher carbon dioxide concentrations, changing characteristics of floods, droughts and potential sea level rise) is considered to gain a more complete picture of potential agriculture impacts. Third, while estimating changes in production is important, economic responses may to some degree buffer against the physical losses predicted, and an assessment is made of these. Food security is dependent not only on production, but also future food requirements, income levels and commodity prices. Finally, adaptation possibilities are identified for the sector. This book is the first to combine these multiple disciplines and analytical procedures to comprehensively address these impacts. The framework will serve as a useful guide to design policy intervention strategies and investments in adaptation measures.